Analisis Spasial Sebaran Sekolah di Kecamatan Warungkondang Kabupaten Cianjur Provinsi Jawa Barat - Handayani, Ayu; Wibowo, Adi (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
Schools are one of the facilities that are needed by the community in a residential area. Even distribution of educational facilities is a benchmark for achieving one of the goals of educational planning. This study aims to determine the distribution of elementary and junior high schools in Warungkondang District, Cianjur Regency and the pattern of school distribution using the descriptive method of NNA analysis.(Nearest Neighbor Analysis) andthe coordinates of the school location are sourced from Google Earth. The results of this study indicate that the distribution of elementary and junior high schools in the Warungkondang sub-district is quite even, the schools that are most widely spread are in Jambudipa Village while the village with no school units is in Bunisari Village and the pattern of school distribution is carried out in 32 locations of Public/Private Elementary and Middle Schools including uniform pattern category (spread).This means that most of the schools are located in densely populated areas in the east and the distribution of these schools is usually located near or along the road network.